2014
DOI: 10.1007/s00128-014-1212-y
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate Resistant Penicillium coffeae: A Potential Fungus for Soil Bioremediation

Abstract: Bioremediation is an effective method for the treatment of major metal contaminated sites. Fungi were isolated from soil samples collected from different arsenate contaminated areas across India. An isolate, Penicillium coffeae, exhibited resistance to arsenate up to 500 mM. Results indicated that pretreatment of biomass with alkali (NaOH) enhanced the percentage of adsorption to 66.8 % as compared to that of live and untreated dead biomass whose adsorption was 22.9 % and 60.2 % respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The reusability of biomaterial, the ability to detect very less concentrations of toxic metals in water, the high removal efficiency, no production of secondary compounds, low operating costs, and short operation times are some advantages of biosorption over other methods . Various biomaterials including plant biomass, agricultural waste, bacteria, fungi, and algae have been used to confiscate As from aqueous solutions . Other conventional methods described above have several technical and economical limitations due to which the biosorption process is gaining attention.…”
Section: As Removal Methodsmentioning
confidence: 99%
“…The reusability of biomaterial, the ability to detect very less concentrations of toxic metals in water, the high removal efficiency, no production of secondary compounds, low operating costs, and short operation times are some advantages of biosorption over other methods . Various biomaterials including plant biomass, agricultural waste, bacteria, fungi, and algae have been used to confiscate As from aqueous solutions . Other conventional methods described above have several technical and economical limitations due to which the biosorption process is gaining attention.…”
Section: As Removal Methodsmentioning
confidence: 99%
“…Explorations into filamentous fungi such as Penicillum [ 92 , 95 ], Fusarium [ 93 ], Trichoderma [ 94 ], Humicola [ 96 ], and Aspergillus [ 93 , 95 ] showed notable resistance to high arsenic concentrations. Screening of As(V)-contaminated agricultural soil in India revealed that a strain of Penicillium coffeae can tolerate As(V) concentrations of up to 37,461 ppm in vitro [ 92 ]. The fungus was also able to tolerate the same concentration of As(V) under basic conditions, whether living, dead, or as treated biomass.…”
Section: Recently Isolated Arsenic Tolerant Microorganisms and Approa...mentioning
confidence: 99%
“…Oil spills Bovio et al [134] Penicillium citrinum Chromium Zapana-Huarache et al [135] Penicillium coffeae Arsenic Bhargavi, Savitha [136] (Contd...)…”
Section: Penicillium Citreonigrummentioning
confidence: 99%